Dormitory Education from the Aspect of Effective Dormitory Management - Lasmi, Hardiyanti; Arafah, H. Muhammad (Journal La Edusci, 2024)
This research aims to find out about good dorm management. The type of research used is qualitative research with a literature study or literature review approach. The data collection technique used is a literature study, where researchers obtain it from journals, books and other printed media that are in accordance with the research objectives. The results of this research are that dormitory management consists of 4 management functions, namely 1. Planning; each person in charge of the room makes rules for each room to maintain order, 2. Organizing; make detailed assignments for dormitory residents, 3. Implementation; implement the program that has been created and 4. Supervision; Activities carried out to see the process of dormitory management that is ongoing or being implemented.